The effect of ice slushy ingestion and mouthwash on thermoregulation and endurance performance in the heat - Burdon, C. A.; Hoon, M. W.; Johnson, N. A.; Chapman, P. G.; O'Connor, H. T. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
The purpose of this study was to establish whether sensory factors associated with cold-beverage ingestion exert an ergogenic effect on endurance performance independent of thermoregulatory or cardiovascular factors. Methods: Ten males performed three trials involving 90 min of steady state cycling (SS; 62% VO2max) in the heat (32.1 ± 0.9 °C, 40 ± 2.4% relative humidity) followed by a 4 kJ/kg body mass time trial (TT). During SS, participants consumed an identical volume (260 ± 38g) of sports beverage (7.4% carbohydrate) every 15 min as either ice slushy (-1 °C; ICE), thermoneutral liquid (37 °C; CON), or thermoneutral liquid consumption with expectorated ice slushy mouthwash (WASH). Results: Rectal temperature, hydration status, heart rate, and skin blood flow were not different between trials. Gastrointestinal (pill) temperature was lower in ICE (35.6 ± 2.7 °C) versus CON (37.4 ± 0.7 °C, p = .05). Heat storage tended to be lower with ICE during SS (14.7 ± 8.4W.m-2, p = .08) and higher during TT (68.9 ± 38.6W.m-2, p = .03) compared with CON (22.1 ± 6.6 and 31.4 ± 27.6W.m-2). ICE tended to lower the rating of perceived exertion (RPE, 12.9 ± 0.6, p = .05) and improve thermal comfort (TC, 4.5 ± 0.2; p = .01) vs. CON (13.8 ± 1.0 and 5.2 ± 0.2 respectively). WASH RPE (13.0 ± 0.8) and TC (4.8 ± 0.2) tended to be lower versus CON (p = .07 and p = .09 respectively). ICE improved performance (18:28 ± 1:03) compared with CON (20:24 ± 1:46) but not WASH (19:45 ± 1:43). Conclusion: Improved performance with ICE ingestion likely resulted from the creation of a gastrointestinal heat sink, reducing SS heat storage. Although the benefits of cold-beverage consumption are more potent when there is ingestion, improved RPE, TC, and meaningful performance improvement with WASH supports an independent sensory effect of presenting a cold stimulus to the mouth.